Agronomic evaluation of unacidulated and partially acidulated Chilembwe rockphosphates for clover seed production - Haque, I.; Lupwayi, N.Z.; Ssali, H. (1998)
Phosphorus (P) is required to improve soil fertility for food and feed produciton in sub-Saharan Africa, but the high cost of conventional, water-soluble P fertilizers limits their use by resource-poor farmers. Rockphosphates are a low-cost alternative. The effectiveness, in terms of seed production, of unacidulated (RP), 25 percent partially acidulated (PARP25), and 50 percent partially acidulated (PARP50) Chilembwe rockphosphate relative to triple superphosphate (TSP) applied at 0 to 80 kg P ha-1 to Trifolium quartinianum L. on a Vertisol in the Ethiopian highlands was evaluated. The fertilizers were applied once and their effects were followed in four consecutive clover crops. Clover seed yields without applied P were below 260 kg ha-1 in the four years of the study. With P applicaiton, seed yields reached as high as 490 kg ha-1. Over all the four crops, RP was 43 percent, PARP25 was 100 percent and PARP50 was 71 percent as effective as TSP in increasing clover seed yields. The corresponding relative responses in seed P contents were 56,100 and 78 percent for RP, PARP25 and PARP50, respectively. The substitution rates in seed yields were 18 percent for RP, 100 percent for PARP25 and 50 percent for PARP50 while those for seed P were 31 percent for RP, 100 percent for PARP25 and 61 percent for PARP50. Significant (P<0.05) effects of P on clover seed yields and P contents were observed only suitable for clover seed production in these soils. However, the partially acidulated products of this rockphosphate were more effective and could be used to elevate the P status of the P deficient Vertisols and increase forage production for increased and sustainable crop and livestock productivity.